The Developmental Psychology of Psychopathology - Vaknin, Samuel, 1961-; Rangelovska, Lidija (Salt Lake City, UT : Project Gutenberg, 2005)
"The Developmental Psychology of Psychopathology" by Samuel Vaknin is a scientific publication written in the early 21st century. This work explores the intricate relationship between childhood development and the emergence of narcissistic and psychopathic features in adulthood, emphasizing how familial dynamics, particularly parental interactions, contribute to these psychological conditions. The opening of the book establishes the groundwork for discussing the narcissistic personality, particularly through the lens of parental influence. It begins with an analysis of the narcissist's atypical emotional landscape$1 (Bhow they seek validation from others while simultaneously viewing them as mere sources of admiration. Vaknin further delves into early relational patterns shaped by parental figures, detailing how these relationships can lead to either healthy self-esteem or maladaptive narcissism. The text introduces complex concepts regarding self-identity, emotional detachment, and the pivotal role of formative experiences in the context of childhood development, illustrating how these elements can culminate in various mental health disorders. (This is an automatically generated summary.)s
Release date is 2005-06-01
Keywords: Narcissism; Psychology, Pathological; Developmental psychology